Cultura de Paz, Educação e Meditação com Jovens em Fortaleza- Ceará - Sampaio, Daniela Dias Furlani (2012)
The main target of our research is the program “Fortaleza em Paz" which calls for collective meditation. Thus, our work is the result of an educational experience with teenagers from school Joaquim Antonio Albano, which is a public professional and educational institution in Fortaleza - Ceará. Discussions were facilitated and as result of them, the perceptions of teachers and students about the “Fortaleza em Paz" program, in that institution, were collected. The choice of this theme is grounded in the belief that this practice can greatly change the attitude and thinking of young people and educators in the educational environment as well as their positions on the environment in which they live, urging them to a culture of peace. The present study has a qualitative nature and an ethnographic view. Literature search, interviews, observations and workshops on culture of peace were conducted with the study subjects. The workshops of culture of peace were used as the main methodological resource. The essential on the promotion of workshops for peace is the creation of discussion forums that enable the construction of summaries to know. This happens in group, reinforcing the idea of collective peace. From the expressions of the young, obtained by means of speeches, drawings, texts, it could be realized that they announce some "benefits" in relation to attend the event of meditation in the school, such as promoting the quality of life, welfare, health, and reduce levels of violence in the city. There was improvement in personal well-being, concentration in class, family relationship and the educational environment and better school performance. Besides the psychological and spiritual benefits obtained in the practice of daily meditation, we believe in the importance of announcing successful examples in terms of education for peace. It could be seen that the “Fortaleza em Paz" program can be used as a teaching strategy in favor of a holistic education. In this sense, the experience of the Culture of Peace workshops can in many ways, encourage reflection and development of persons involved in the meditation group at school about the impact of this experience in their lives. Then, it can be concluded that the technique of meditation brought positive consequences for the group studied. This is only one among many possibilities of work culture of peace. The path to an education that respects the scale of the human being and form, indeed, citizens can exercise their full potential, it is certainly a long journey. The exciting journey experimented in this research will hopefully be a step in that direction, toward building a Culture of Peace, which will also be consolidated mainly through education.